Dispute over the 1974 MoU Box between Indonesia and Australia: How MoU Legally Binding in Two Countries? - Noviana Putri, Salwa; Fazari, Ariq; Ari Widodo, Nico; Fatahillah, Faishal; Dwinugraha, Satria (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
This study aims to delineate the legal authority of Memorandum of Understanding (MoUs) within the jurisdictions of Indonesia and Australia, particularly concerning the resolution of international civil law disputes. The research employs a normative juridical approach, utilizing legal reviews and secondary data for support. The findings reveal that in civil law states, notably Indonesia, MoUs are regarded as binding agreements in accordance with the "Agreement is Agreement" perspective as per Article 1338 (1) of the Civil Code. Conversely, common law states, such as Australia, generally perceive MoUs as non-legally binding. However, an MoU may attain validity and binding status if it fulfills the six stipulated requirements outlined in Australian contract law. To address the dispute surrounding the 1974 MoU BOX between Indonesia and Australia, resolution options include examining international civil law rules based on primary and secondary links or resorting to an international arbitral tribunal.